KERAGAAN KEDELAI (Glycine max.) GENERASI M1 HASIL MUTASI VARIETAS DEGA 1 DENGAN BEBERAPA KONSENTRASI Ethyl Methane Sulphonate - Aslim Rasyad; Bondan Fiarahman (UIR Press, 2022)
Increasing soybean productivity required some effort as one is to develop new high-yielding varieties or improve existing varieties. To obtain an improved variety, one needs to obtain a population with high genetic variability to ease the selection of new suitable cultivars. In this study, we used to induce mutations using chemical mutagen, ie, Ethyl Methane Sulphonate (EMS), to increase the variability. This research had been conducted in the Plant Breeding Laboratory and the experimental farm of Riau University. Seeds of Dega-1 Variety were soaked in the solution of EMS in buffer phosphate within several concentrations ie, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, and 700 ppm. The seed then were washed with aquadest to clean the remaining EMS solution and then planted together by initial Dega-1 as the control in the field experiment using a completely randomized design (RAL) with four replications. Parameters observed were plant height, number of internodes the age of flowering, age of harvest, number of pods per plant, number of filled pods per plant, number of seeds per plant, seed weight per plant, number of seeds per pod, and type of growth, flower color, and pod color. Population variances were calculated by Microsoft Excel software. The homogeneity of the variance was tested with HOV by the procedures of Levene’s test. The results showed that the induction of mutations with 200 ppm of EMS increased genetic variance in M1 generation compared to the Dega 1 variety for the most quantitative character, including plant height, number of pods per plant, number of filled pods per plant, number of seeds per plant, and seed weight per plant. Induce that the mutation by EMS solution, on the other hand, didn’t change all qualitative characters.